2020
DOI: 10.3390/foods9060798
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality Characteristics and Shelf Life of Meat and Growth Performance in Goose Fed Diets Supplemented with Vitamin E

Abstract: The present study was carried out to investigate the effect of dietary vitamin E on growth performance, cellular immunity, carcass characteristics, and meat quality in geese. Sixty-four one-day-old male geese were selected from 1200 goose chicks with the same average body weight (92.5 ± 2.5 g) and subjected to two treatments (basal diet or control and basal diet plus 120 mg/kg vitamin E supplement) with 4 replicates (8 geese per replicate) for 8 weeks. After slaughter, goose meat was aerobically packed in poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Vitamin E (VE) is the main antioxidant in egg yolk lipid terminating the lipid peroxidation chain by reacting with lipid peroxides and making them stable [2]. The use of excess dietary vitamin E in poultry' feed has been shown to increase the growth performance, the meat nutritional value in terms of the fatty acid composition, and the shelf life [13]. Łukaszewicz et al [14] determined the effect of feed supplementation with organic selenium and vitamin E on chemical composition and sensory characteristics of Japanese quail (coturnix japonica) eggs and reported that feeding Japanese quail with selenium and vitamin E reduces the concentration of fat in eggs and the concentration of cholesterol in yolk, while increasing the levels of selenium, protein, and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin E (VE) is the main antioxidant in egg yolk lipid terminating the lipid peroxidation chain by reacting with lipid peroxides and making them stable [2]. The use of excess dietary vitamin E in poultry' feed has been shown to increase the growth performance, the meat nutritional value in terms of the fatty acid composition, and the shelf life [13]. Łukaszewicz et al [14] determined the effect of feed supplementation with organic selenium and vitamin E on chemical composition and sensory characteristics of Japanese quail (coturnix japonica) eggs and reported that feeding Japanese quail with selenium and vitamin E reduces the concentration of fat in eggs and the concentration of cholesterol in yolk, while increasing the levels of selenium, protein, and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments were including different levels of vitamin E (VE, 30 or 120 mg kg −1 ) and Se sources (SS, sodium selenite; SP, Sel-Plex); 2 gram/bird per day; 3 feed conversion ratio = feed intake/egg mass;4 Hen-day egg production = (total number of eggs/number of live layers) × 100; 5 average egg weight = total weight of collected eggs/total number of collected eggs;6 Egg mass = [egg production (%) × average egg weight (g)] × 100;7 Egg specific gravity = egg weight/[0.9680 × (egg weight -Shell weight) + (0.4921 × shell weight)];8 Albumen percentage = (albumen weight/egg weight) ×100; 9 Yolk percentage = (yolk weight/egg weight) × 100;10 Yolk Albumen ratio = yolk weight/albumen weight;11 Haugh unit = 100 log [albumen height (mm)-1.7 weight of the egg (g)0.37+ 7.57];12 Eggshell percentage = (dried shell weight/egg weight) × 100;13 Egg surface area (mm) = 3.9782 × egg weight (g);14 Egg shape index = (egg width/egg length) × 100. Values (means) within a row with uncommon letters are significantly (p < 0.05) different.…”
mentioning
confidence: 99%
“…Oxidation reactions, particularly in lipids, can remarkably affect stability and decline the shelf life of meat and meat products (Nemati et al., 2020). TBARS values as an efficient indicator in evaluating lipid oxidation in meat products associated with the accumulation of secondary products from lipid peroxides and hydro‐peroxides (Lorenzo et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In birds, the body weight at birth, egg production and egg yolk color traits are quantitative traits, presumed to be controlled by numerous genes or loci in the genome with minor effects, and also influenced by multiple factors, including genetic factors, diet, housing, environment, management, disease, and other factors, such as environment, diet, housing practice (Dikmen et al, 2016;Mwaniki et al, 2018;Gou et al, 2020;Nemati et al, 2020;Zhao et al, 2020). Compared with other technologies, whole-genome resequencing technology is a high-throughput sequencing approach with efficient, accurate, full information characteristics (Fuentes-Pardo and Ruzzante, 2017).…”
Section: Introductionmentioning
confidence: 99%